Proses Rekrutmen, Seleksi, Pelatihan, Penempatan dan Kinerja Karyawan - A.A. Inten Suastika Dewi; Gede Sri Darma (Universitas Pendidikan Nasional, 2017)
ABSTRACTThe purpose of this study is 1. Knowing the effect of the implementation process of recruitment to training. 2. Determine the influence of the implementation process of the selection of the training. 3. Determine the influence of the implementation process of recruitment of placement. 4. Determine the influence of the implementation process of the selection of the placement. 5. Determine the influence of the implementation process of recruitment to performance. 6. Determine the influence of the implementation process of the selection of the performance. 7. Determine the influence of the implementation process of the placement of the performance. Data collection technique used questionnaires to 127 customers of PT Bank Mandiri (Persero) Tbk Branch Kuta. Data were analyzed by Structural Equation Model (SEM) with AMOS version 22Results found that 1 indicates that the effect of variable recruitment to training is significant. (2) show that variables influence the selection of the training is significant. (3) shows that the effect of variable recruitment of the placement is significant. (4) indicates that the variable influence the selection of the placement is significant. (5) shows that the effect of variable recruitment to performance is significant. (6) show that variables influence the selection of the performance is significant. (7) shows that the effect of the placement of variables on performance is significant.